Sosialisasi Peningkatan Kemampuan Literasi Bahasa Inggris Dengan Metode Problem Based Learning - Mungkap Mangapul Siahaan; Sanggam Siahaan; Rudiarman Purba; Asima Rohana Sinaga; Apriani Sijabat; Herna Febrianty Sianipar; Christa Voni Roulina Sinaga; Ropinus Sidabutar; Partohap Sihombing (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Improving writing skills is as supporting factor for the success of learning carried out by each teacher. Writing ability comes from the habit of reading and analyzing problems in learning that is carried out every day. The culture of writing is still far from being a habit for teachers of SMP Negeri 3 Jorlang Hataran. Therefore, the University of HKBP Nommensen Pematangsiantar University team has carried out a community service at SMP Negeri 3 Jorlang Hataran, Jalan Besar Parapat, Nagori Bah Sampuran. district Jorlang Hataran, Simalungun Regency, North Sumatra where this service aims to socialize methods of improving English literacy skills using the problem based learning method for teachers of SMP Negeri 3 Jorlang Hataran. This service has been received with good response and was appreciated by the Principal of SMP Negeri 3 Jorlang Hataran. The results obtained from this service were 76.7% of participants who stated that they were satisfied with this service. It is hoped that with this activity, there will be a good cooperation established between the University and the school to develop the quality of teachers in order to create the higher quality education.